Pengaruh Green Accounting dan Biaya Lingkungan terhadap Profitabilitas pada Perusahaan Sektor Pertambangan yang Terdaftar di BEI Tahun 2020–2023 - Astrid Ananda Renaldi; Kasan K. Suantha (Jurnal Ekonomi Manajemen Akuntansi, 2025)
This research aims to analyze the impact of green accounting and environmental costs on the profitability of mining companies listed on the Indonesia Stock Exchange (BEI) during the period from 2020 to 2023. A quantitative descriptive method with an associative quantitative approach was employed, relying on secondary data obtained from the companies' annual reports available on the official BEI website. The study sample consisted of 11 companies, and data analysis was conducted using IBM SPSS version 29. The findings reveal that the implementation of green accounting significantly and positively contributes to the profitability of these companies. Conversely, expenditures on environmental costs did not demonstrate a significant impact on profitability. Nevertheless, when examined together, both variables collectively influence an increase in the companies' profitability.